Pengaruh Pemberian Zeolit Alam Teraktivasi terhadap Sifat Kimia Tanah Podsolik - Lita Hertati; Hairil Ifansyah; Syaifuddin Syaifuddin (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2022)
Podsolic soil in South Kalimantan has a low fertility rate including pH, organic matter, cation exchange capacity (CEC), solubility P, and has a high solubility of aluminum (Al) and iron (Fe). It causes fixation P by Al and Fe in the form of Al-P and Fe-P, which makes P difficult to dissolve in the soil. Zeolite is an ameliorant that is capable of improving soil chemical properties based on its ability to carry out ion exchange, adsorption, absorb molecules, increase fertilizer efficiency, increase soil CEC, and the availability of Ca, K, and P ions, which can reduce aluminum content. The purpose of this study was to identify the pattern of relationships caused by application of activated natural zeolite on Podsolic soil against pH, CEC, available P, soluble Fe, and exchangeable Al. This study was a pot experiment weighing 0.5 kg of soil, carried out in a greenhouse and arranged using CRD a single factor . The incubation period was carried out for eight weeks with three replications. The results showed that there was a relationship between the zeolite dose activated against the available P (the linear regression equation Y = 0.6 + 0.032 X, R2 = 0.4969, and r = 0.7006*), while the doses of zeolite had no significant effect on pH, CEC, soluble Fe, and exchangeable Al.